1989
DOI: 10.1164/ajrccm/140.3.593
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hypertonic Saline-induced Bronchoconstriction by Terfenadine and Flurbiprofen: Evidence for the Predominant Role of Histamine

Abstract: We investigated the possible inhibitory effects of terfenadine, a histamine H1-receptor antagonist, and flurbiprofen, a cyclooxygenase inhibitor, on the bronchoconstrictor effect of inhaled 3.6% hypertonic saline in a randomized, double-blind study. Nine mildly asthmatic subjects with a history of exercise-induced asthma took part. This was conducted, first as a dose-response study and, second, as a time-course study. In the dose-response study, the provocative dose of saline-laden air causing a 25% fall in FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 4 publications
4
36
1
Order By: Relevance
“…In contrast, aerosolized indomethacin was reported to inhibit ultrasonically nebulized distilled water (UNDW)-induced airway obstruction in asthmatic subjects [40]. Our results are consistent with those of FINNERTY and co-workers [35], who concluded that prostaglandins played a minor role in the development of HIB in subjects with asthma. The fact that indomethacin does protect against UNDW but does not attenuate responses to hypertonic aerosols suggests that these two stimuli operate via different pathways.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, aerosolized indomethacin was reported to inhibit ultrasonically nebulized distilled water (UNDW)-induced airway obstruction in asthmatic subjects [40]. Our results are consistent with those of FINNERTY and co-workers [35], who concluded that prostaglandins played a minor role in the development of HIB in subjects with asthma. The fact that indomethacin does protect against UNDW but does not attenuate responses to hypertonic aerosols suggests that these two stimuli operate via different pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Although mediator release has been implicated in AIB [12,19,21,33] and HIB [34][35][36], the role of biochemical mediators in the initiation of these responses remains controversial. The protection provided by antihistamines [19,34,35], mast cell "stabilizers" [36], cyclooxygenase inhibitors [11,19], and leukotriene receptor antagonists [21,37,38] suggest at least a partial role for these mediators in the development of AIB and HIB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the inability of a b 2 -agonist to afford complete protection, little is known about the protective measures against the effects of hypertonic saline in COPD. In contrast, studies in patients with asthma have revealed significant protection by different types of drugs, such as antihistamines and nedocromil, suggesting mast cell activation and neural pathways as potential mechanisms [7][8][9].…”
mentioning
confidence: 99%
“…Most but not all studies of asthmatic subjects implicate a role for histamine in AIB (table 1). Terfenadine inhibits AIB [102] and HAIB [146] similarly. Studies of allergic rabbits also implicate a role for histamine in AIB (table 1).…”
Section: Calcium Antagonistsmentioning
confidence: 99%